Effect of a cognitive training program and Jacobson relaxation technique on anxiety and resilience of students in the operation room: A randomized control trial - Shadi Dalvand; Forouzan Ahmadi; Ali Akbari; Maryam Shirdel (Journal of Nursing Advances in Clinical Sciences)
This study was conducted to compare the effect of the cognitive training program and the Jacobsen relaxation technique on anxiety and resilience in the operating rooms of hospitals affiliated with the Hamedan University of Medical Sciences. This study is a randomized clinical trial on 96 operating room students at Hamedan University of Medical Sciences in 2022. The samples were randomly assigned to the cognitive training program, relaxation technique, and control group. Demographic questionnaires, Beck's anxiety, and Conor and Davidson's resilience were completed. Students were subjected to six weekly intervention sessions in the cognitive training program group. In the Jacobsen relaxation technique group, the students were trained in the philosophy and how to practice it practically. They were asked to do this at least once a day. Checklists were provided to the students to report doing this work within six weeks. No intervention was performed in the control group. At the end of six weeks, all three groups completed questionnaires again, and the data were entered into SPSS version 24 software for analysis. The anxiety score of the cognitive training and Jacobson relaxation group after the training significantly decreased compared to before the training (P>0.001). The resilience score of the cognitive training and Jacobson relaxation group increased significantly after the training compared to before the training (P>0.001). The results of this study show that the cognitive training program and Jacobson relaxation can reduce anxiety, increase resilience, improve mental health, and improve the teaching and learning process.